(untitled) (Modern education and development, 2024)
Maqolada xitridiomitsetlar sinfining umumiy tasnifi, morfologik xususiyatlari va ko‘payish usullari yoritilgan. Ularning jinsiy va jinsiz ko‘payish usullari turli sharoitlarga moslashuvni ta’minlaydi. В статье описаны общая классификация класса хитридиомицетов, морфологические особенности и способы размножения. Их способы полового и бесполого размножения обеспечивают адаптацию к различным условиям. The article describes the general classification of the class of chytridiomycetes, morphological features and methods of reproduction. Their methods of sexual and asexual reproduction ensure adaptation to different conditions.